Предмет: Алгебра,
автор: Apolinaria001
Решите уравнение:
(3х-2)²=(2х+1)(2х-1)+5х²-7
Ответы
Автор ответа:
1
(3х-2)²=(2х+1)(2х-1)+5х²-7
9x²-12x+4=4x²-1+5x²-7
9x²-12x+4=9x²-8
-12x=-8-4
-12x=-12
x=-12:(-12)
x=1
9x²-12x+4=4x²-1+5x²-7
9x²-12x+4=9x²-8
-12x=-8-4
-12x=-12
x=-12:(-12)
x=1
Похожие вопросы
Предмет: Английский язык,
автор: DanilShaebakov
Предмет: Русский язык,
автор: 1234567890987655
Предмет: Русский язык,
автор: КатеринаАнгел04
Предмет: Химия,
автор: Andrijo
Предмет: Музыка,
автор: sonyaiv7